Fakultas Ekonomi Universitas Muhammadiyah Surakarta - Wuryaningsih DL, Wuryaningsih DL (Universitas Muhammadiyah Surakarta, 2012)
Bank is one financial institution that provides a variety of financial services that are used as the place where the transaction. As intermediary between parties who have surplus funds and those who need funds required banks to healthy financial performance. The research was conducted with the aim to analyze the financial performance of the financial industry inIndonesia. The ratio used to analyze the financial performance of the banking industry inIndonesia is Liquidity Ratios, Solvability Ratios, Profitability Ratios. The sampling method usedwas purposive sampling method. Of the population were 28 listed banking industry in IndonesiaStock Exchange, taken seven banking companies that meet the criteria of the sampl e, the companies included in the banking industry, the company that went public before the date of December 31, 2008 and a banking company that publishes financial reports on a regular basis at 31 December 2008.2009. The results showed that: (1) Liquidity ratio: (a)the financialperformance of banks in 2008-2009 categorized not good, measured from the current ratio,because the value of the current ratio is less than 200% is equal to 94% in 2008 and 97% in 2009, (b) the financial performance of banks in 2008-2009 categorized not good, as measured by the quick ratio, quick ratio because the value is less than 100% is equal to 94% in 2008 and 97% in 2009, (c)the financial performance of banks in 2008-2009 categorized not good, measured from the cash ratio, because the value of the cash ratio less than 100% which is 28% in 2008 and 32% in 2009.(2) solvency ratio: (a)the financial performance of banks in 2008-2009 categorized solvable measured by debt to net worth, because the value of debt to net worth of mo re than 25% in the amount of 942% in 2008 and 840% in 2009, (b) the financial performance of banks in 2008-2009 categorized solvable, measured by total assets to net worth, because the value of total assets to net worth of more than 25% is equal to 1082% i n 2008 and 970% in 2009, (c) the financial performance of banks in 2008-2009 categorized insolvable measured from fixed assets to net worth, as value of fixed assets to net worth less than 25% at 15% in 2008 and 12% in 2009.(3) The ratio of earnings: (a) the banking company for the year 2008-2009 is still a very small benefit only Rp 0.0185,00 in 2008 and Rp 0.0223,00 in 2009, (b) the banking company for the year 2008-2009 is still a very small benefit from its own capital only Rp 0.15,00 in 2008 and Rp 0.17,00 in 2009